2021
DOI: 10.1021/acs.nanolett.1c02657
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Strategy for Reinforcing Flexible Ceramic Membranes

Abstract: Herein, we present a facile reinforcement method for the large-scale fabrication of highly flexible, mechanically stable, temperature-resistant ceramic lightweight membranes based on the cross-linked assembly of zirconia–silica (ZrO2–SiO2) nanofibrous and montmorillonite (MMT) nanosheets through electrospinning and a subsequent calcination process. The resulting MMT@ZrO2–SiO2 membranes exhibit high flexibility with a bending rigidity of 0.2 cN mm–1, robust mechanical performance with a tensile strength of up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…This enhanced rigidity of composites is caused by the in situ crosslinking reaction among porous silica materials in the fiber frameworks. 17,20 The mesoporous silica could be the extra bonding between the fiber joints to improve the overall mechanical robustness of composites. A previous study showed that the flexible composite has a compressive strength of 2.19 MPa, while the additive manufactured composite with 20 wt % fiber has a tensile strength of 15.84 MPa.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This enhanced rigidity of composites is caused by the in situ crosslinking reaction among porous silica materials in the fiber frameworks. 17,20 The mesoporous silica could be the extra bonding between the fiber joints to improve the overall mechanical robustness of composites. A previous study showed that the flexible composite has a compressive strength of 2.19 MPa, while the additive manufactured composite with 20 wt % fiber has a tensile strength of 15.84 MPa.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…h SEM image of the MMT@ZrO 2 -SiO 2 nanofibers. The inset is the corresponding optical image of soft nanofibrous membrane [ 164 ]. i TEM image of MMT@ZrO 2 -SiO 2 nanofiber [ 164 ].…”
Section: Mechanical Behavior Of Electrospun Snfsmentioning
confidence: 99%
“…The inset is the corresponding optical image of soft nanofibrous membrane [ 164 ]. i TEM image of MMT@ZrO 2 -SiO 2 nanofiber [ 164 ]. j Stress–strain curves of ZrO 2 -SiO 2 and MMT@ZrO 2 -SiO 2 nanofibrous membranes [ 164 ].…”
Section: Mechanical Behavior Of Electrospun Snfsmentioning
confidence: 99%
See 2 more Smart Citations